2006
DOI: 10.1109/tnb.2005.864015
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Colloidal Nanotopography on Initial Fibroblast Adhesion and Morphology

Abstract: Abstract-Colloidal lithography offers a simple, inexpensive method of producing irregular nanotopographies, a pattern not easily attainable utilizing conventional serial writing processes. Colloids with 20-or 50-nm diameter were utilized to produce such an irregular topography and were characterized by calculating the percentage area coverage of particles. Interparticle and nearest neighbor spacing were also assessed for the individual colloids in the pattern. Two-way analysis of variance (ANOVA) indicated sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
39
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 44 publications
4
39
0
Order By: Relevance
“…Our observations on cell number, morphology, and adhesion on the 3D sharp-tip Nanoposts were consistent with the results reported on the columnar nanostructures fabricated by polymer demixing [6,11] or colloidal lithography [7][8][9]15], including a clear interaction between cell's filopodia and the nanofeatures [6,7,9,11]. However, it should be noted that the pattern periodicity (100 nm -2 μm) and the tip diameter (50 nm -1 μm)…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our observations on cell number, morphology, and adhesion on the 3D sharp-tip Nanoposts were consistent with the results reported on the columnar nanostructures fabricated by polymer demixing [6,11] or colloidal lithography [7][8][9]15], including a clear interaction between cell's filopodia and the nanofeatures [6,7,9,11]. However, it should be noted that the pattern periodicity (100 nm -2 μm) and the tip diameter (50 nm -1 μm)…”
Section: Discussionsupporting
confidence: 91%
“…To date, there have been several studies on the nanotopographical effects on cell behaviors, including human fibroblasts [6][7][8][9]11,15,18,19,23]. Our observations on cell number, morphology, and adhesion on the 3D sharp-tip Nanoposts were consistent with the results reported on the columnar nanostructures fabricated by polymer demixing [6,11] or colloidal lithography [7][8][9]15], including a clear interaction between cell's filopodia and the nanofeatures [6,7,9,11].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…For example, previous studies have demonstrated that initial fibroblast adhesion moderately increased on silica surfaces with a colloidal nanotopography. 4 However, some studies have also demonstrated adverse effects of nanostructures on cell adhesion, 5 and there has a been lack of understanding as to why some nanofeatures increase cellular functions while others may not. The authors' group has observed that increased cellular (eg, osteoblasts, fibroblasts, endothelial cells) functions can result on nanotopographies which possess altered wettability due to the presence of such nanofeatures.…”
mentioning
confidence: 99%